2022
DOI: 10.3390/agronomy12102514
|View full text |Cite
|
Sign up to set email alerts
|

New Biodegradable Mulching Films for Strawberry (Fragaria × Ananassa Duch.): Effects on the Volatile Profiles of the Fruit

Abstract: The effects of mulching films on the profiles of volatile organic compounds (VOCs) from two strawberry cultivars, namely Elide and Sabrina, were evaluated by headspace solid-phase micro-extraction coupled to gas chromatography mass spectrometry (HS-SPME/GC-MS). Strawberries were grown on two biodegradable mulching films, named N5 and N18, in comparison to black polyethylene (PE). PCA models, separately performed on the VOCs dataset of the two cultivars, showed that the observations for each of the three mulchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the Candonga cultivar, linalool, together with α-muurolene and butanoic acid methyl esters, was reported to be an indicator of fruit ripeness, as it modifies during ripening processes. The authors assessed that its concentration could offer information about the optimal harvest time, even if it seems to not be transferable to other cultivars [22,26]. Similar conclusions were drawn by Padilla-Jiménez et al [6], who reported terpenes as the earliest maturation stage markers for the Frontera variety; in fact, they participate in the protection of the plant during its initial development.…”
Section: An Overview Of Strawberry Aromamentioning
confidence: 61%
See 3 more Smart Citations
“…In the Candonga cultivar, linalool, together with α-muurolene and butanoic acid methyl esters, was reported to be an indicator of fruit ripeness, as it modifies during ripening processes. The authors assessed that its concentration could offer information about the optimal harvest time, even if it seems to not be transferable to other cultivars [22,26]. Similar conclusions were drawn by Padilla-Jiménez et al [6], who reported terpenes as the earliest maturation stage markers for the Frontera variety; in fact, they participate in the protection of the plant during its initial development.…”
Section: An Overview Of Strawberry Aromamentioning
confidence: 61%
“…In particular, linalool, and nerolidol were detected as the main volatile terpenoids in cultivated ripe strawberries, whereas α-pinene, β-myrcene, α-terpineol, β-phellandrene, and myrtenyl acetate were mostly identified in wild strawberries [5]. Linalool was the most occurrent VOC in selected research articles, and it was the most abundant in the Elide strawberry variety [26]. The Candonga and Festival varieties were richer in terpenes than the Camarosa cultivar [31].…”
Section: An Overview Of Strawberry Aromamentioning
confidence: 95%
See 2 more Smart Citations